The impact of coronavirus lockdown on oral healthcare and its associated issues of pre-schoolers in China: an online cross-sectional survey - Chang Liu; Shuang Zhang; Chenzheng Zhang; Baojun Tai; Han Jiang; Minquan Du (BMC, 2021)
Abstract Background The sudden outbreak of coronavirus disease (COVID-19) epidemic influenced people's daily life. During lockdown of Wuhan city, the oral health and its associated issues of preschool children were investigated and guidance for dental clinics when the epidemic were controlled in the future were also provided. Methods A national online survey was conducted among preschool children and completed by their caregivers. The questionnaire related to children's oral health status and care behaviour, caregivers' attitudes. The information was statistically analyzed between Wuhan residents and others residents. Results 4495 valid questionnaires were collected. In oral health status, during Wuhan lockdown, 60.8%, 35.5% and 18.3% children had self-reported dental caries, toothache and halitosis respectively. In oral health attitudes, respondents who would increase attention to oral health was more than that would decrease. In oral hygiene behaviour, compared to non-Wuhan children, the children in Wuhan became more active in brushing their teeth. In utilization of dental services in the future, less Wuhan residents would choose to have dental visit directly, 28.5% Wuhan residents and 34.7% non-Wuhan residents agreed all of procedures could be done if proper protected. Conclusions Oral health status and associated issues of preschool children in Wuhan were significantly different from that of others during lockdown of Wuhan city and in the future. Effective measures should be taken as early as possible to protect children's oral health.